The comparative performance of selected agribusiness companies and cooperatives in the Western Cape, South Africa - Sikuka, Wellington (Stellenbosch : University of Stellenbosch, 2010)
Thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Agriculture (Agricultural Economics) at Stellenbosch University